Safety around fire - Raatma, Lucia (Mankato, Minn. : Bridgestone Books, 1999)
Describes different sources of fire and how to stay safe around fires both indoors and outside.
Includes bibliographical references (p. 23) and index.
Keywords: Fire prevention -- Juvenile literature; Fire -- Juvenile literature; Fire prevention; Safety